(untitled) (Altre Modernità, 2018)
In China, the genre (Bhatia 1993) of news commentary has had a key role in the evolution of the country’s politics since the end of the 19th century, when modern journalism started to develop under the late Qing dynasty (De Giorgi 2001). In contemporary press, news commentaries (xinwen pinglun) can be divided into two main sub-genres: commentary on current affairs (shiping) and editorial (shelun ??). While their structure and communicative purposes are similar, the main difference lies in the (in)visibility of the author. Shiping are signed by the commentator and include a brief profile to qualify them as an expert. Shelun are anonymous, since the opinions presented are the paper’s voice (Cheng 2008, Ding 2009, Du 2013). Starting from the late 90s, as a consequence of the commercialisation of the sector and a growing demand for original views in the press, papers have increasingly relied on independent contributors (ziyou zhuangaoren) for commentaries on current affairs and editorials (Shen 2003, Gongyang 2008, Lupano 2017). Drawing on a series of interviews made to Chinese independent commentators between 2008 and 2015, this contribution aims to discuss the effects that the (in)visibility of the author has on the commentary’s authoritativeness and political influence, and the degree of independence with which opinions can be expressed, in a media environment that is still attentively controlled by the political authority (Qian and Bandurski 2011, Young 2013).